WINDERFUL Wind and INfrastructures Dominating Eolian Risk For Utilities and Lifelines - Ricciardelli, Francesco; Sepe, Vincenzo; Bartoli, Gianni (Proceedings e report, 2004)
WINDERFUL (an acronym for Wind and INfrastructures: Dominating Eolian Risk For Utilities and Lifelines) is the title of a research project carried out by eight Italian Universities from the end of 2001 to the end of 2003. The project was centred on how "to keep a city running and ensuring quality services during and after major windstorms", avoiding "major failures" of engineering facilities and main infrastructures. The book reports the main results obtained in the project, and for each typology the tool for assessing its reliability are discussed, together with the criteria for its improvement.